Adult Onset Vitiligo: Multivariate Analysis Suggests the Need for a Thyroid Screening. (22nd September 2016) - Lazzeri, L.; Colucci, R.; Cammi, A.; Dragoni, F.; Moretti, S.
Abstract : Background . There are limited epidemiological studies evaluating the effect of age at onset on disease features in vitiligo. Objectives . To identify factors associated with adult onset vitiligo in comparison with childhood onset vitiligo. Patients and Methods . We retrospectively collected medical records of 191 patients. Such records included clinical examination, personal and familial medical history, laboratory evaluations, concomitant vitiligo treatment and drug assumption. Results . 123 patients with a disease onset after the age of 40 (adult onset vitiligo) were compared with 68 patients who developed vitiligo before the age of 12 (childhood onset vitiligo). Multivariate analysis revealed that personal history of thyroid diseases (P = 0 . 04 ; OR 0.4), stress at onset (P = 0.002 ; OR = 0.34), personal history of autoimmune thyroid disease (ATD) (P = 0.003 ; OR = 0.23), and thyroid nodules (P = 0.001 ; OR 0.90) were independently associated with adult onset vitiligo, whereas family history of dermatological diseases (P = 0.003 ; OR = 2.87) and Koebner phenomenon (P < 0.001 ; OR = 4.73) with childhood onset vitiligo. Moreover, in the adult onset group, concomitant thyroid disease preceded vitiligo in a statistically significant number of patients (P = 0.014 ). Conclusions . Childhood onset and adult onset vitiligo have different clinical features. In particular, ATD and thyroid nodules were significantly associated with adult onset vitiligo, suggesting that a thyroid screening should be recommended in this group of patients.